Fenomena Generasi Muda Dalam Aktivitas Ritual Keagamaan Hindu di Pura Parahyangan Jagat Guru Tangerang Selatan: (Studi Hiperealitas Jean Boudrilard) - Raharjo, Sukirno Hadi; Budiastra, Ketut; Suhardi, Untung (Jayapangus Press, 2023)
The trend of globalization became a social vortex that swept through all aspects of life, This reality must have been of concern to the younger generation of Hindus that preserved the Hindu religious ritual. These social symptoms are certainly an integral part of trying to get the impression that the Hindu youth has forgotten and that only citizens are involved in any religious activity. This study aims to explain the impact globalization has on the interest of young people in Hindu religious rituals. This is a descriptive qualitative research. Informants in this study, as many as 10 of the young generation in tangerang selatan. Metode data collection by gathering various reference both primary and secondary sources of relevance to the younger generation hindu and religious rites.The result of indicate that the tends to lead to the context of the activity Which suggests that the younger generation of Hindus in the southern city of Tangerang tend to do more of a good job, compared to the understanding related to the Hindu religious ritual.It indicates that there is still a need for coaching the further religious activities of the Hindu ritual, especially in the complete implementation of understanding of the meaning of the Hindu religious ritual.